Planejamento da expansão dos sistemas de distribuição: metodologia para a consideração de pequenas centrais hidreléticas - Brunno Viana dos Santos Sant`anna (2009)
The large number of small hydroelectric power plants in operation in Brazil, the growing number of future plants and the necessity of electrical available resources optimization, demand the development of new procedures adjusted to this new scenario. In this direction, this thesis proposes an innovative methodology dedicated to the Expansion Planning of Distribution Systems. It allows the consideration of the small hydroelectric plants in the planning studies, and its adoption results benefits to power utilities and consumers.